British Journal of Anaesthesia: a leading publication and a registered charity. (January 2023) - Lambert, David G.; Struys, Michel M.R.F.; Howell, Simon
Summary: The British Journal of Anaesthesia organisation is a registered charity comprised of two interlinked missions: provision of impactful publications and funding the generation and dissemination of research to the wider anaesthetic community. This centenary editorial highlights our charitable activity that covers funding of research infrastructure, meeting support and funding of a diverse portfolio of international research grants.